2015
DOI: 10.1371/journal.pone.0143797
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tannic Acid, Green Tea and Red Wine on hERG Channels Expressed in HEK293 Cells

Abstract: Tannic acid presents in varying concentrations in plant foods, and in relatively high concentrations in green teas and red wines. Human ether-à-go-go-related gene (hERG) channels expressed in multiple tissues (e.g. heart, neurons, smooth muscle and cancer cells), and play important roles in modulating cardiac action potential repolarization and tumor cell biology. The present study investigated the effects of tannic acid, green teas and red wines on hERG currents. The effects of tannic acid, teas and red wines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Figure b shows the G‐V curves with controls for bufalin (10 and 100 μ M ) and terfenadine (100 n M ). Terfenadine is a well‐established hERG blocker, and we used the Terfenadine (100 n M ) as a positive control drug to compare the inhibitory efficiency with the bufalin (10, 100 μ M ) . G‐V curves were established from the tail currents at −60 mV, and bufalin 100 μ M significantly shifted the V 1/2 toward more negative potentials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure b shows the G‐V curves with controls for bufalin (10 and 100 μ M ) and terfenadine (100 n M ). Terfenadine is a well‐established hERG blocker, and we used the Terfenadine (100 n M ) as a positive control drug to compare the inhibitory efficiency with the bufalin (10, 100 μ M ) . G‐V curves were established from the tail currents at −60 mV, and bufalin 100 μ M significantly shifted the V 1/2 toward more negative potentials.…”
Section: Resultsmentioning
confidence: 99%
“…In molecular genetic tests, G418 is used to screen the stably transfected cells. In the experiment of preparing the HEK293 cells stably transfected with hERG, neo gene exists in these cells and makes these cells grow in a selective medium containing G418 .…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have suggested that TA possessesanti-lipogenic, anticarcinogenic, antiinflammatory, antioxidant, and scavenging activities (Gali et al, 1992;Chu et al, 2016). TA has some potent pharmacological effects, including myocardial protection (Hu et al, 2015;Zhang et al, 2017a;Zhang et al, 2017b), a decrease in L-type Ca 2+ currents in isolated mice ventricular myocytes (Zhu et al, 2016), and a vasodilatory effect via activation of K + channels expressed in HEK293 cells (Chu et al, 2015;Zhang et al, 2016a). However, the relevance of the protective results of TA on chronic MF is not well-defined.…”
Section: Introductionmentioning
confidence: 99%
“…TA is a glucoside comprising gallic acid polymers that form part of the hydrolysable tannins found to possess anti-oxidative properties that may contribute to their cancer preventive, chemotherapeutic, and anti-inflammatory properties [11][12][13]. In vivo, TA and other green tea polyphenols inhibited the mammary tumour virus promoter, whereas in vitro the proliferation of specific cancer cell lines was inhibited and induced apoptosis [14]. TA has been revealed to exert a significant liver-protective effects in mice with CCl4-induced liver fibrosis [15].…”
Section: Introductionmentioning
confidence: 99%